ERIKSON'S PSYCHOSOCIAL STAGES OF DEVELOPMENT IN TURKISH PROVERBS (Third Sector Social Economic Review, 2022)
In this study, which aims to examine the ""Psychosocial Development Theory"" developedby Erik H. Erikson within the scope of proverbs, information was given about the psychosocial development periods and the connection of Turkish proverbs with Erikson's psychosocial development period characteristics was evaluated. In this study based on content analysis, the proverbs in the Turkish Language Association Proverbs and Idioms Dictionary database were compiled by associating with the characteristics of Erikson's psychosocial development periods and included in the study by considering their meanings. In the study, many proverbs that support the prominent features in Erikson's ""Psychosocial Development Periods"" were found in Turkish proverbs.389 proverbs have been identified, emphasizing the important characteristics of the developmental stages and the factors affecting the development. It is noteworthy that the highest concentration with 131 proverbs is in the period of success versus inadequacy, which is the 4th period, and then in the period of identity versus role confusion, which is the 5th period with 61 proverbs.
Keywords: Psychological Counseling; Proverbs; Personality Development; Erikson; Psychosocial Stages of Development